An RGD motif on SARS-CoV-2 Spike induces TGF-β signaling and downregulates interferon - Gracie, Nicholas P.; Aggarwal, Anupriya; Luo, Rachel; Spicer, Mitchell; Idrees, Sobia; Ashley, Caroline L.; Alca, Sibel; Ison, Timothy; Steain, Megan C.; Patel, Karishma; Siddiquee, Rezwan; Low, Jason K. K.; et al. (Journal of virology, 2025)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) presents an ongoing public health challenge as a cause of acute illness and post-acute sequelae of COVID-19 (PASC, or long COVID). Our study identifies the RGD integrin-binding motif in the spike (S) protein as central to the cellular response to SARS-CoV-2, leading to the expression of the pleiotropic cytokine TGF-β and disabling of antiviral immunity. This work further supports the S protein-to-integrin complex signaling axis as a potential therapeutic target. The RGD motif might also be a valid target for treating PASC given the increasing body of evidence implicating the presence of persistent S protein in the etiology of this disease.